A meta-analysis of the prevalence of gestational diabetes in patients diagnosed with obstetrical cholestasisAJOG Global Reports at a Glance - Manoj Mohan, MRCOG; Sanjay Swargathmadhom Prabhu, MRCOG; Abdul Kareem Pullattayil, MSIt; Stephen Lindow, FRCOG (AJOG Global Reports, 2021)
BACKGROUND: Gestational diabetes and obstetrical cholestasis are common clinical conditions seen in clinical practice. There is evidence suggesting a coexisting relationship that could have a potential clinical implication related to stillbirth outcomes. OBJECTIVE: This study aimed to determine the prevalence of gestational diabetes in women with obstetrical cholestasis. STUDY DESIGN: A predefined protocol with a literature search was used to obtain all possible articles. A systematic review and meta-analysis of observational studies with quantifiable data published since 2010 were performed. Articles were evaluated and included in the study with specified criteria for the risk of bias using the Newcastle-Ottawa Scale. A meta-analysis was performed using Meta-analysis of Observational Studies in Epidemiology specifications to determine the prevalence of gestational diabetes in women with obstetrical cholestasis. RESULTS: A total of 16,748 patients with obstetrical cholestasis from 21 studies were included. The prevalence of gestational diabetes in women with obstetrical cholestasis was 13.9% (20 studies analyzed). Gestational diabetes was more common in women with obstetrical cholestasis than in women without obstetrical cholestasis (odds ratio, 2.129; 95% confidence interval, 1.697–2.670;10 studies). Gestational diabetes is twice more common in women with severe cholestasis than in women with mild cholestasis (odds ratio, 2.168; 95% confidence interval, 1.429–3.289; 4 studies). CONCLUSION: There is an increase in the prevalence of gestational diabetes among women diagnosed with obstetrical cholestasis. Compared with women with mild cholestasis, the increased risk of gestational diabetes in women with severe cholestatis is more than doubled. This suggests that the 2 conditions may have some biological similarities that affect clinical outcomes.